Explore The Factors Influencing Linguistic Variation And Change: A Multifaceted Analysis - Sohaib Saeed Hameed; Moharib Najm Nayef (Global Scientific Publishing, 2024)
Studying language in all its facet’s structure, acquisition, variety, and change—is the bread and butter of linguistics. This study article delves into the complex field of linguistics by exploring several aspects of language, such as phonetics, syntax, semantics, sociolinguistics, and psycholinguistics, with the purpose of exploring the effect of geography on linguistic variety and change. We will investigate the everchanging character of language, its historical development, and its effects on human thought and speech by drawing from a variety of academic fields. To better understand how language impacts our lives, this article compiles recent study results and provides insights into the many facets of linguistics.
Keywords: Linguistics; Semantics; Academic